Multilingualism and Interculturality in international or interregional projects and work environments. - Michelin, Anais Marie Christelle (Jihočeská univerzita, 2022)
The master thesis aimed to find out structural and individual strategies of managing multilingualism and interculturality within the BOKU - International Relations working team. In the first part of this work I set up a theoretical research framework focused on the following key topics : intercultural management, intercultural competence, intercultural teams, communication and challenges. The last part of the theoretical part describes the existing models about the University of Natural Resources and Life Sciences working environment I referred to. Empirical data were collected using data triangulation through document analysis and qualitative semi-structured interviews to demonstrate the structural and individual strategies of managing multilingualism and interculturality of six BOKU-IR team members. They were then analyzed by sequences and transcribed with the software FOLKER according to the convention GAT2. The results show an overview of the intercultural management and the strategies used to deal with multilingualism and interculturality within the BOKU- International Relational working environment.
Multilingualism and Interculturality in international or interregional projects and work environments.
Keywords: Multilingualism; interculturality; intercultural management; intercultural competences; intercultural communication; linguistic and cultural adaptations; team culture; intercultural and multilingual work environments; working together.; Multilingualism; interculturality; intercultural management; intercultural competences; intercultural communication; linguistic and cultural adaptations; team culture; intercultural and multilingual work environments; working together.